2021
DOI: 10.3390/cells10112988
|View full text |Cite
|
Sign up to set email alerts
|

Roles of G Protein-Coupled Receptors (GPCRs) in Gastrointestinal Cancers: Focus on Sphingosine 1-Shosphate Receptors, Angiotensin II Receptors, and Estrogen-Related GPCRs

Abstract: It is well established that gastrointestinal (GI) cancers are common and devastating diseases around the world. Despite the significant progress that has been made in the treatment of GI cancers, the mortality rates remain high, indicating a real need to explore the complex pathogenesis and develop more effective therapeutics for GI cancers. G protein-coupled receptors (GPCRs) are critical signaling molecules involved in various biological processes including cell growth, proliferation, and death, as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 182 publications
(296 reference statements)
0
14
0
Order By: Relevance
“…GPCRs play important roles in mediating cell proliferation, migration and invasion, angiogenesis, cell death, and cell survival. GPCRs also play key roles in the growth and development of cancer [ 37 ]. In HPV-associated cancers such as cervical cancer, GPCRs can be activated by the interaction of chemokines CXCR4 and ACKR3 with glycosaminoglycans of the extracellular matrix (ECM), acting as targets of oncogenic pathways at the cellular level of cancer cells and TME [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs play important roles in mediating cell proliferation, migration and invasion, angiogenesis, cell death, and cell survival. GPCRs also play key roles in the growth and development of cancer [ 37 ]. In HPV-associated cancers such as cervical cancer, GPCRs can be activated by the interaction of chemokines CXCR4 and ACKR3 with glycosaminoglycans of the extracellular matrix (ECM), acting as targets of oncogenic pathways at the cellular level of cancer cells and TME [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of Wnt11, which activates the noncanonical Wnt pathway promotes the proliferation, invasion, and migration of CRC cell lines [ 52 ]. Some GPCRs such as S1PR3, S1PR5, and AT1R are associated with tumorigenesis, proliferation, invasion, and migration of CRC cells [ 53 ]. Cho et al reported that upregulation of Hippo pathway genes is related to poor prognosis in patients with CRC [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…An exciting perspective toward studying cancers in the light of GPCRs is the aspect of sexual dimorphisms affecting the disease incidence and mortality. A keen interest has grown in the scientific community to explore the role of estrogen and estrogen‐related GPCRs, like the G‐protein‐coupled estrogen receptor (GPER1) which is involved in the initiation and progression of gastrointestinal (GI) cancers 145 . It is particularly fascinating that hormone replacement therapy (HRT) or the use of oral contraceptives is positively associated with a lower risk of certain cancers such as CRC, endometrial, and ovarian cancer 149‐151 .…”
Section: Gpcrs In Cancer and Gpcromicsmentioning
confidence: 99%
“…GPCRomics has helped in the identification of GPCRs that are often mutated and are the hotspots for accumulating DNA damage across different cancer types, particularly in solid tumors, such as adenocarcinomas, cervical, ovarian, breast, prostate, and bladder cancers 144 . Interestingly, a handful of GPCRs exert bidirectional effects on tumorigenesis in various cancer types exhibiting both pro‐tumorigenic and anti‐tumorigenic depending on TME characteristics, variable affinities of their ligands, and diverse implications of signaling pathways downstream 145 . For example, Sphingosine‐1‐phosphate receptor 5 (S1PR5) overexpression in colorectal cancer (CRC) cell lines promotes colon cancer proliferation and invasion via activation of NF‐κB/indoleamine 2,3 dioxygenase 1 (IDO1) axis 146 .…”
Section: Gpcrs In Cancer and Gpcromicsmentioning
confidence: 99%
See 1 more Smart Citation